PERTIMBANGAN HAKIM DALAM MENJATUHKAN PUTUSAN PEMIDANAAN TERHADAP PIMPINAN ANGGOTA DPRD YANG MELAKUKAN TINDAK PIDANA KORUPSI - Fitriati Fitriati; Bisma Putra Pratama; Azhamu Suwaril (UNES Law Review, 2023)
The formulation of criminal acts of corruption is set forth in Article 2 and Article 3 of Law Number 31 of 1999 concerning Eradication of Corruption Crimes. Judge's Considerations in Sentence Decisions Against the Leaders of DPRD Members Perpetrating Corruption Crimes in Decision Number 40/Pid.Sus/2020/PN.Pdg and Decision Number 41/Pid.Sus/2020/PN.Pdg Juridically based on the indictment, evidence, the demands and beliefs of the Judge, the Defendant's actions fulfill the elements contained in Article 3 of Law Number 20 of 2001 Juncto Article 55 of the Criminal Code, namely the act of abuse of authority to benefit oneself and or other people which results in losses to the state which are carried out jointly. While non-juridical considerations are burdensome considerations, as the chairman and deputy chairman of the DPRD already know that their actions violate the rules. The mitigating considerations were that the Defendant had returned state financial losses and admitted his actions. Criminal Application in the Sentence Decision Against the Leaders of DPRD Members Perpetrating Corruption Crimes in the Decision is based on Article 3 UUPTPK juncto Article 55 paragraph (1) to 1 of the Criminal Code. In Decision Number 40/Pid.Sus/2020/PN.Pdg Criminal against the Defendant with imprisonment for 2 (Two) Years and 4 (Four) Months and a fine of Rp. 50,000,000.- (Fifty Million Rupiah). The additional sentence imposed is the obligation to pay replacement money in the amount of IDR 190,014,090.00 (one hundred and ninety million fourteen thousand and ninety rupiah) in decision number 41/Pid.Sus/2020/PN.Pdg the judge sentenced the defendant to imprisonment for 1 (one) year and a fine of Rp. 50,000,000.- (Fifty Million Rupiah).